Continuous flow microwave processing of peanut butter: A (hypothetical) computational process design study with experimental validation. (December 2022) - Coskun, Eda; Ozturk, Samet; Topcam, Huseyin; Karatas, Ozan; Li, Rui; Wang, Shaojin; Mert, Behic; Erdogdu, Ferruh
Abstract: The increase in foodborne pathogen cases in low moisture foods has raised a significant food safety concern for food industry. One of the most significant outbreaks related with these food products was observed in 2008–2009 due to Salmonella problem in peanut butter. This issue was recently observed again for a multinational case. Challenges of conventional thermal processing due to the lower thermal conductivity – diffusivity value and higher viscosity, microwave (MW) heating might be an efficient processing while the non-uniform heating is a challenging drawback. Therefore, the objective of this study was to develop a mathematical model for MW processing of peanut butter and present industrial scale designs for continuous flow processing. For this purpose, the mathematical model was first experimentally validated using a lab-scale system and validated with experimental data. Following this, continuous flow MW process design studies were carried out with different holding tube configurations to obtain a temperature increase to enable decontamination and improve the temperature uniformity. These design simulations provided a better understanding to enhance the process efficiency of high viscosity low moisture peanut butter samples and for design and optimization of continuous flow MW processing. Highlights: A computational model for MW processing of peanut butter was developed. The developed computational model was experimentally validated. Industrial scale MW process studies were carried out. Continuous flow MW system for processing peanut samples was presented. Effect of rotation and holding tube configurations were explored in continuous MW systems.